2020
DOI: 10.1080/15325024.2020.1835386
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Stress and Depression: Examining Social Media, Traditional Media, and Interpersonal Communication

Abstract: Prior research has found that infectious disease outbreaks such as that of the coronavirus disease (COVID-19) are associated with adverse mental health, especially among individuals with more exposure to COVID-19. Less studied are the possible relationships of media use and interpersonal communication as they relate to COVID-19 exposure and mental health outcomes. In the current study, a structural equation model tested the direct and indirect relationships of a variety of proximity variables including COVID-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
51
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(58 citation statements)
references
References 34 publications
4
51
0
3
Order By: Relevance
“…It is possible that more explicit stress communication is a marker of participants' higher distress in front of the COVID-19 emergency. In line with a previous study, in fact, interpersonal communication with significant others about COVID-19 was associated with greater perceived stress (First et al, 2020).…”
Section: Discussionsupporting
confidence: 90%
“…It is possible that more explicit stress communication is a marker of participants' higher distress in front of the COVID-19 emergency. In line with a previous study, in fact, interpersonal communication with significant others about COVID-19 was associated with greater perceived stress (First et al, 2020).…”
Section: Discussionsupporting
confidence: 90%
“…Among the various media exposure forms, only social media was significantly associated with higher acute stress and the odds of probable ASD. The result is consistent with the previous findings that social media users had more psychological problems compared with traditional media users during the COVID-19 pandemic ( Chao et al, 2020 ; First et al, 2020 ). Social media was usually regarded as the most extensively used medium for acquiring information about COVID-19 without time and site limits.…”
Section: Discussionsupporting
confidence: 92%
“…For example, Rodgers et al (2012) found that the use of traditional media (e.g., television) was related to more psychological distress among adults compared with new media (e.g., Internet) following the March 2011 Japan Earthquake. However, First et al (2020) found that social media use was associated with higher levels of stress and depression than traditional media use following the COVID-19 pandemic. Therefore, the associations between media exposure forms and acute stress responses deserve further exploration.…”
Section: Introductionmentioning
confidence: 94%
“…As of February 2021, the respiratory disease caused by this novel virus (COVID-19) has resulted in multiple waves of outbreaks in the U.S. resulting in over 440,000 deaths and more than 25 million cases ( https://covid19.who.int/region/amro/country/us ). In addition to death and physical illness, COVID-19 has exerted a significant public mental health impact, resulting in increased individual stress, anxiety, depression, and grief reactions ( Eisma & Tamminga, 2020 ; First et al, 2020 ).…”
mentioning
confidence: 99%